International e-learning for farmers: Gender and Agriculture - International Potato Center (International Potato Center, 2021)
This video explains why gender matters in agriculture through the example of potato growers in Georgia. The targeted audience are women and men farmers across the world. Gender equity in agricultural development projects cannot be achieved without women and men farmers’ awareness of their own gender norms and their willingness to change. This video will facilitate farmers’ involvement in discussions and decisions on how the project addresses women’s and men’s different needs and constraints, enabling the project teams to implement gender-responsive participatory planning for achieving equitable and inclusive outcomes.